Frailty as a dynamic process in a diverse cohort of older persons with dialysis-dependent CKD - Kutner, Nancy G.; Zhang, Rebecca (Frontiers in Nephrology, 2023)
This study examines frailty status evolution observed in a two-year follow-up of a cohort of older persons (age ≥65) with chronic kidney disease (CKD) undergoing maintenance hemodialysis (HD) treatment. Frailty, a geriatric syndrome that connotes a state of low physiologic reserve and vulnerability to stressors, is associated with increased risk for multiple adverse health outcomes in studies of persons with CKD as well as older persons in the general population. The Fried frailty index defines frailty as the presence of 3 or more of 5 indicators—recent unintentional weight loss, slowed gait speed, decreased muscle strength, self-reported exhaustion, and low physical activity. In the seminal work by Fried and colleagues, persons who were characterized by 1-2 of the Fried index criteria were termed “pre-frail” and considered at risk for subsequently becoming frail, potentially providing insight regarding intervention targets that might slow or prevent individuals’ transition from pre-frail to frail status. Other less frequently studied types of transitions may also be informative, including “recovery or reversion” (improvement) by people whose longitudinal assessments indicate movement from frailty to prefrailty or robust, or from prefrailty to robust. These status changes are also a potential source of insights relevant for prevention or remediation of frailty, but research focusing on the various ways that individuals may transition between frailty states over time remains limited, and no previous research has examined varying patterns of frailty status evolution in an older cohort of persons with dialysis-dependent CKD. In a study cohort of dialysis-dependent older persons, we characterized patterns of frailty status evolution by age, sex, race/ethnicity, and treatment vintage; by longitudinal profiles of non-sedentary behavior; and by self-report indicators relevant for dimensions emphasized in the Age-Friendly 4Ms Health System (What Matters, Mobility, Mentation). Our study suggests that strategies to promote resiliency among older persons with dialysis-dependent CKD can be informed not only by frailty status transition that indicates improvement over time but also by older adults’ maintenance of (stable) robust status over time, and we concur that inclusion of both frailty and resilience measures is needed in future longitudinal studies and clinical trials.